(untitled) (Nóema, 2011)
Il presente articolo analizza il rapporto tra filosofia, esperienza ed evento nel pensiero di A.N. Whitehead. L’autrice ripercorre e descrive, a partire dalla critica al concetto di oggetto, la peculiare dialettica di astratto e concreto al centro dalle indagini whiteheadiane sull’esperienza percettiva. Successivamente, viene mostrato come la pratica filosofica differisca da ogni genere di scienza, pur necessitandone in virtù della co-implicazione di oggetto ed evento, astrazione e riconoscimento. Experience and event of truth. Philosophical practice and scientific abstraction in A.N. Whitehead’s thought This article analyzes the relationship between philosophy, experience and event in A.N. Whitehead’s thought. From the critic of the concept of object, the author retraces and describes the peculiar “abstract-concrete dialectic”, at the center of the researches concerning the perceptual experience. Furthermore, according to Whitehead’s later works, she demonstrates how the philosophical practice is different from all other kinds of science, although it requires science itself because of the co-implication of object and event, abstraction and recognition.